Silicic Acid-Mediated Formation of Tannic Acid Nanocoatings - Weber, Florian (Langmuir : the ACS journal of surfaces and colloids, 2019)
Tannic acid (TA) adheres to a broad variety of different materials and forms versatile surface coatings for technical and biological applications. In mild alkaline conditions, autoxidation processes occur and a firm monolayer is formed. Up to now, thicker coatings are obtained in only a cross-linked multilayer fashion. This study presents an alternative method to form continuous TA coatings using orthosilicic acid (Siaq). Adsorption kinetics and physical properties of TA coatings in the presence of Siaq were determined using a quartz-crystal microbalance and nanoplasmonic spectroscopy. An in situ TA layer thickness of 200 nm was obtained after 24 h in solutions supplemented with 80 μM Siaq. Dry-state measurements indicated a highly hydrated layer in situ. Furthermore, chemical analysis by Fourier transform infrared spectroscopy revealed possible complexation of TA by Siaq, whereas UV-vis spectroscopy did not indicate an interaction of Siaq in the autoxidation process of TA. Investigation of additional metalloid ions showed that germanic acid was also able to initiate a continuous coating formation of TA, whereas boric acid prevented the polymerization process. In comparison to that of TA, the coating formation of pyrogallol (PG) and gallic acid (GA) was not affected by Siaq. PG formed continuous coatings also without Siaq, whereas GA formed only a monolayer in the presence of Siaq. However, Siaq induced a continuous layer formation of ellagic acid. These results indicate the specific importance of orthosilicic acid in the coating formation of polyphenolic molecules with multiple ortho-dihydroxy groups and open new possibilities to deposit TA on interfaces